2021
DOI: 10.1161/circulationaha.121.054698
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cardiac Dysfunction During Adjuvant Breast Cancer Therapy (PRADA): Extended Follow-Up of a 2×2 Factorial, Randomized, Placebo-Controlled, Double-Blind Clinical Trial of Candesartan and Metoprolol

Abstract: Background: Adjuvant breast cancer therapy containing anthracyclines with or without anti–human epidermal growth factor receptor–2 antibodies and radiotherapy is associated with cancer treatment–related cardiac dysfunction. In the PRADA trial (Prevention of Cardiac Dysfunction During Adjuvant Breast Cancer Therapy), concomitant treatment with the angiotensin receptor blocker candesartan attenuated the reduction in left ventricular ejection fraction (LVEF) in women receiving treatment for breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 30 publications
0
72
1
5
Order By: Relevance
“…Furthermore, the present study highlights the importance of a longer post-chemotherapy FU period to properly evaluate the benefits of ACEis (and possibly other HF drugs providing neurohormonal blockade) in the primary prevention of chronic ANT-induced cardiotoxicity. This finding might be particularly relevant for studies investigating subjects with a lower cardiotoxic burden associated with currently prescribed maximal cumulative doses of ANT, as was recently highlighted by the results of the extension of the PRADA trial [59].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, the present study highlights the importance of a longer post-chemotherapy FU period to properly evaluate the benefits of ACEis (and possibly other HF drugs providing neurohormonal blockade) in the primary prevention of chronic ANT-induced cardiotoxicity. This finding might be particularly relevant for studies investigating subjects with a lower cardiotoxic burden associated with currently prescribed maximal cumulative doses of ANT, as was recently highlighted by the results of the extension of the PRADA trial [59].…”
Section: Discussionmentioning
confidence: 67%
“…However, no significant benefit was recognizable after assessing the levels of cardiac biomarkers (NT-proBNP or cardiac troponins). Very recently, an extension of this trial has been published [59], where the patients were followed after candesartan withdrawal (up to approximately 2 years from randomization). Notably, no difference in LVEF was observed between candesartan-treated and non-treated patients (p=0.91).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Elkhateeb et al randomized 126 breast cancer patients treated with anthracycline chemotherapy, with or without trastuzumab, to either a combination of enalapril and carvedilol or placebo, and although the intervention group was associated with statistically fewer participants experiencing a reduction in LVEF ≥10% as assessed by cardiac MRI (1.9% vs. 12.5%, p = 0.04), only 24% of patients received trastuzumab and pre-specified subgroup analyses were not performed [ 45 ]. Additionally, the recently published Prevention of Cardiac Dysfunction During Adjuvant Breast Cancer Therapy (PRADA) trial [ 46 ], which assessed the use of ARB’s or beta-blockade to attenuate the decline in LVEF in patients receiving adjuvant anthracycline-containing regimens, only included 27 patients treated with adjuvant trastuzumab. Neither the use of candesartan nor metoprolol was associated with prevention of cardiotoxicity at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…This may provide some theoretical basis for the use of ACEI or β-receptor inhibitors in the prevention of TIC. Several small randomized trials and single-center studies have also reported that ACEI and β-blockers ameliorate chemotherapy-induced cardiotoxicity, but these studies all emphasized high-dose anthracycline-induced cardiotoxicity and have limited clinical applicability in TIC ( 71 , 72 ). In 2016, the MANTICORE 101-Breast randomized clinical trial specifically investigated the pharmacological prevention of TIC and found that Perindopril and Bisoprolol were well-tolerated in the prevention of TIC and attenuated the decrease in LVEF, but trastuzumab-induced left ventricular remodeling was not reversed ( 73 ).…”
Section: Prevention and Treatment Of Ticmentioning
confidence: 99%